PENGARUH PENGEMBANGAN SUMBER DAYA MANUSIA DAN LINGKUNGAN KERJA TERHADAP KINERJA PEMBUAT JAMU PADA INDUSTRI JAMU DI PAMEKASAN - Nabilah Maulidah Az-Zahroh; Mudji Kuswinarno; Yufita Listiana; Zainiyatul Afifah (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2024)
Madura has many small and medium industries (MSMEs) that produce traditional herbal medicine. One of the districts in Madura that has great potential in the production and development of herbal medicine is Pamekasan Regency. In this district, there are traditional herbal medicine businesses in the form of MSMEs in all sub-districts. Despite its great potential, the herbal industry in Pamekasan still faces several challenges that require an increase in the performance of human resources (HR). These challenges encourage modernization which requires an increase in the performance of herbalists, so as to create efficiency and strengthen the existence of the herbal industry or MSMEs in Pamekasan in the herbal market industry. The type of research used is a type of quantitative method. Data collection method through interviews, questionnaires, and literature studies. The analysis techniques used is the multiple linier regression test. The results showed that (1) HR development had a positive and significant effect on the performance of herbalists (2) The work environment has a positive and significant effect on the performance of herbalists. (3) HR development and work environment simultaneously or together affect the performance of herbalists.